الشاعر القاسم بن هُتَيْمِل في آراء النقاد - حيدر, علي; أبو بكر, محمود (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
هذا البحث محاولة للتعريف بواحد من أبرز شعراء القرن السابع الهجري في اليمن، هو القاسم بن علي ابن هُتَيْمِل الضَمَدي، الذي انتظمت حياته طيلة ذلك القرن تقريباً، إذ عاش الفترة بين(605 - 696هـ)، حسب الاستنتاجات المستقاة من شعره الذي سجّل فيه أحداث عصره، وقضى حياته متنقلاً بين اليمن والحجاز، مادحاً أمراء موطنه في المخلاف السليماني، وأمراء الحجاز، وشيوخ القبائل، وأئمة الزيدية، وسلاطين بني رسول في اليمن، وقد حمل بذلك رسالة الأدب وخلّف وراءه ثروة لغوية وأدبية وفكرية، ممثلة في ديوانه الضخم، الذي ما يزال بكراً وجديراً بالدراسة والتحليل. وفي هذا التعريف الذي يرسم صورة مصغرة عن الشاعر دعوة كريمة إلى الدارسين والمهتمين بالأدب، بأن يولوا وجوههم شطر جنوب الجزيرة العربية (اليمن) التي لم ينل شعراؤها-ولاسيما شعراء عصر الدولة الرسولية- ما يستحقونه من الدراسة والاهتمام. This research tries to introduce ‘AL-Qasim bin Ali bin Hutimel Addamadi’, one of the leading poets of the seventh Hegira century in Yemen. As the conclusions drawn from his poems, which record the events of his time, he almost witnessed the whole century since he lived between (605 - 696 A.H). He spent his life moving between Yemen and Hejaz, praising his homeland princes in Almikhlaf Assulimani, princes of Hejaz, the tribe elders, Zaidi imams, and sultans of Bani Rasul in Yemen. Therefore, he carried the message of literature and left behind a linguistic literary intellectual wealth represented in his huge collection of poems, which is still virgin and worthy of study and analysis. In this research, which briefly introduces the poet, there is a kind invitation to students and those interested in literature to pay attention toward the Southern Arabian Peninsula (Yemen), whose poets have not had what they deserve from study and attention, especially during the era of Arrasuli State.